2021
DOI: 10.3390/healthcare9060651
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Prevalence and Risk Factors in a Village in Northeastern Romania—A Population-Based Screening—The First Step to Viral Micro-Elimination

Abstract: (1) Background: The World Health Organization adopted a strategy for the Global Health Sector on Viral Hepatitis in 2016, with the main objective of eliminating hepatitis C virus (HCV) by 2030. In this work, we aimed to evaluate the prevalence of HCV infection and risk factors in a Romanian village using population-based screening as part of the global C virus eradication program. (2) Methods: We conducted a prospective study from March 2019 to February 2020, based on a strategy as part of a project designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
0
0
0
4
Order By: Relevance
“…55,56 More recent Romanian studies reported anti-HCV prevalence of .77% to 2.64% (Table 3; Figure 1). 55,[57][58][59] The lowest anti-HCV prevalence was reported by Butaru et al who tested 15 383 subjects in Oltenia and found 119 (.77%) of them being anti-HCV positive. Half (49%) of these individuals were unaware of their status.…”
Section: [France Belgium the Netherlands Luxembourg Germany Switzerla...mentioning
confidence: 99%
“…55,56 More recent Romanian studies reported anti-HCV prevalence of .77% to 2.64% (Table 3; Figure 1). 55,[57][58][59] The lowest anti-HCV prevalence was reported by Butaru et al who tested 15 383 subjects in Oltenia and found 119 (.77%) of them being anti-HCV positive. Half (49%) of these individuals were unaware of their status.…”
Section: [France Belgium the Netherlands Luxembourg Germany Switzerla...mentioning
confidence: 99%
“…Mặc khác, yếu tố dịch tễ liên quan đến nhiễm HCV thuộc nhóm nhân khẩu học và hành vi tiếp xúc mầm bệnh cũng khác nhau tùy thuộc vùng địa lý. Sự phân bố tỷ lệ nhiễm HCV khác nhau ở từng nhóm tuổi, và giới tính theo nghiên cứu tại Thành phố Hồ Chí Minh [4], nhưng khảo sát của Huiban L. và cộng sự [5] chưa tìm thấy sự khác biệt trên. Hầu hết các công bố trong và ngoài nước đều cho thấy tiền sử truyền máu và sử dụng thuốc dạng tiêm lâu dài là yếu tố nguy cơ độc lập của nhiễm vi rút viêm gan C [4], [5] , [6], [7].…”
Section: đặT Vấn đềunclassified
“…Sự phân bố tỷ lệ nhiễm HCV khác nhau ở từng nhóm tuổi, và giới tính theo nghiên cứu tại Thành phố Hồ Chí Minh [4], nhưng khảo sát của Huiban L. và cộng sự [5] chưa tìm thấy sự khác biệt trên. Hầu hết các công bố trong và ngoài nước đều cho thấy tiền sử truyền máu và sử dụng thuốc dạng tiêm lâu dài là yếu tố nguy cơ độc lập của nhiễm vi rút viêm gan C [4], [5] , [6], [7]. Bên cạnh đó, hành vi tiếp xúc như sử dụng chung kim tiêm, dụng cụ vệ sinh cá nhân, xăm mình, xỏ khuyên và có hơn một bạn tình liên quan đến lây nhiễm HCV trong cộng đồng [4], [6] nhưng chưa được ghi nhận trong nghiên cứu tại Romania [5].…”
Section: đặT Vấn đềunclassified
See 2 more Smart Citations